A Review on: Visual Recognition Through Object Bank - Sharma, Amrit Kumar (International Journal of Computer Sciences and Engineering, 2015)
This report consists of a literature review of papers dealing with visual recognition using different techniques. Several papers that brought contribution to this field are summarized, analysed and compared. Different papers uses different moreover similar concepts for image/object recognition and their work brought average results in this field. By using the novel concept of Object Bank (OB) very good progress over image/object recognition has been done over recent years. Here we are stipulating the concept of Object Bank for high level visual recognition by using different Support Vector Machine (SVM) classifiers.